Seismic interpretation of the Cretaceous unconformities and sequences in the Middle Magdalena Valley and the western margin of the Eastern Cordillera, Colombia - Guerrero, Jairo; Montes, Luis; Jaillard, Etienne; Kammer, Andreas (Comptes Rendus. Géoscience, 2021)
Geoscientists commonly focus on Tertiary units to understand the Andean uplift and deformation of the eastern Cordillera of Colombia, whereas the Cretaceous evolution remains poorly known. Cretaceous units are exposed in western Eastern Cordillera, but outcrops are scarce in the Middle Magdalena Valley. Recent seismic acquisition programs and new wells drilled through the Cretaceous succession led to a better understanding of unconformities and sequences in both the Middle Magdalena Valley and the western flank of the Eastern Cordillera.This paper identifies unconformities bounding seismic sequences and deciphers Cretaceous structural deformation in the Middle Magdalena Valley and western Eastern Cordillera based on the interpretation of sizable seismic reflection sections and well information. The analysis of sedimentary sequences and unconformity surfaces allowed identification of stages of pre-Eocene deformation. Regional correlations of sequences and unconformities recognized here with those identified by other authors support the occurrence of Cretaceous regional tectonic events.